2018
DOI: 10.3847/1538-4357/aab9ad
|View full text |Cite
|
Sign up to set email alerts
|

The Keck/OSIRIS Nearby AGN Survey (KONA). I. The Nuclear K-band Properties of Nearby AGN*

Abstract: We introduce the Keck Osiris Nearby AGN survey (KONA), a new adaptive optics-assisted integralfield spectroscopic survey of Seyfert galaxies. KONA permits at ∼ 0.1 resolution a detailed study of the nuclear kinematic structure of gas and stars in a representative sample of 40 local bona fide active galactic nucleus (AGN). KONA seeks to characterize the physical processes responsible for the coevolution of supermassive black holes and galaxies, principally inflows and outflows. With these IFU data of the nuclea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 82 publications
4
30
1
Order By: Relevance
“…Since the thermal AGN emission arises from reprocessing of more energetic photons, a correlation between the nuclear 2-10 keV X-ray nuclear and NIR fluxes is expected. This correlation has been observed in previous works for more luminous AGNs Alonso-Herrero et al 2001;Burtscher et al 2015;Müller-Sánchez et al 2018). Figure 8 shows the correlation for NIR and nuclear 2-10 keV X-ray luminosities and fluxes for our data -we include all 15 galaxies, but code the data points according to the robustness of their detections, with magenta points being the most robust.…”
Section: Robustness Of Detection and Final Nir Fluxessupporting
confidence: 80%
See 1 more Smart Citation
“…Since the thermal AGN emission arises from reprocessing of more energetic photons, a correlation between the nuclear 2-10 keV X-ray nuclear and NIR fluxes is expected. This correlation has been observed in previous works for more luminous AGNs Alonso-Herrero et al 2001;Burtscher et al 2015;Müller-Sánchez et al 2018). Figure 8 shows the correlation for NIR and nuclear 2-10 keV X-ray luminosities and fluxes for our data -we include all 15 galaxies, but code the data points according to the robustness of their detections, with magenta points being the most robust.…”
Section: Robustness Of Detection and Final Nir Fluxessupporting
confidence: 80%
“…This emission may arise at the dust sublimation radius, where dust can be heated up to 2000 K (Laor & Draine 1993;Kobayashi et al 1993;Alonso-Herrero et al 1996;Riffel et al 2009;Kishimoto et al 2011). This NIR emission also seems to be correlated with X-ray emission (Kotilainen et al 1992;Alonso-Herrero et al 1996;Civano et al 2012;Burtscher et al 2015;Müller-Sánchez et al 2018), supporting this dust emission picture. In lower luminosity systems, the development of NIR integral field spectrographs has enabled spectral separation of stellar and AGN emission (Davies et al 2007;Riffel et al 2010;Burtscher et al 2015;Müller-Sánchez et al 2018).…”
Section: Introductionmentioning
confidence: 68%
“…Guainazzi et al (2005) classified its nucleus as a Compton-thin but highly absorbed (N H ∼ 5 × 10 23 cm −2 ) source. Müller-Sánchez et al (2018) suggested the presence of a double nucleus in this galaxy based on the nonpoint-like shape of their 2.12 µm continuum.…”
Section: Ngc 7465 (Mrk 313)mentioning
confidence: 87%
“…On one hand, spatially resolved spectroscopy based on [O III] kinematics mapped the velocity structure in the NLR (e.g., Crenshaw & Kraemer 2000;Fischer et al 2013). More detailed studies of gas kinematics and star formation became possible thanks to the integral field spectroscopy (e.g., Nesvadba et al 2006;Harrison et al 2014;Karouzos et al 2016a,b;Bae et al 2017;Wylezalek et al 2017;Müller-Sánchez et al 2018;Freitas et al 2018). On the other hand, more systematic studies of [O III] kinematics were based on the spatially integrated spectra obtained from large sur-veys since a large sample of AGNs can be utilized, revealing that outflows are prevalent, particularly among luminous AGNs (e.g., Mullaney et al 2013;Bae & Woo 2014;Woo et al 2016;Shen et al 2016;Woo et al 2017;Zhang & Feng 2017;Wang et al 2018;DiPompeo et al 2018).…”
Section: Introductionmentioning
confidence: 99%